A. I. Neusykhin and his conception of transitional period: perception and interpretations - M. ZEMLIAKOV (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article’s objective is a comprehension of important concept in Russian medieval history — the conception of ‘prefeudal’ (transitional) period developed in A. I. Neusykhin’s scholarly works. Along with the analysis of the emergence and contents of this conception, author observes the issue of perception and adoption of A. I. Neusykhin’s scientific ideas in his disciples’ essays, his colleagues’ and our contemporaries’ researches, both in Russia and abroad. This scholarly work shows that the conception of transitional period wasn’t an idea developed by Neusykhin at first time. Some scientifists had used this model in 30 th—50th years of XXth century to discover early stages of history of East Slavs (for example, B. D. Grekov). A. I. Neusykhin personally advanced to this conception in his researches very long. His first experience of survey of transition between Antiquity and Middle Ages has been dated from 1922; it was an article about A. Dopsch’s ideas. In our article we not only analyse the essence of Neusykhin’s conception, but also give our consideration to those historians which have been developed the idea oftransition period concerning Scandinavia and Byzantium (A. Ja. Gurevic, M. J. Sjuzjumov). Their theses bear a likeness to conception of A. I. Neusykhin, but we pay special attention to difference between those scholarly works. This paper first represents a significant number of unknown documents from Neusykhin’s private archive.